The origins of Oleksii Dovhiy's poetic space - Строкаль, Олександр Миколайович (Київський національний університет імені Тараса Шевченка, 2020)
The article analyzes the nature of linguistic explication of the ideas of Oleksii Dovhiy's lyrical hero about the features of the universe and the organization of the universe. The author deals with such issues of general theoretical significance as the concept and linguistic worldview. During the research it was found out that Oleksii Dovhiy's poetry combines the revelation of a son who prides himself on the glory of generations, paternal and grandfather's moral principles, confession of a fighter for the Fatherland, a manuscript of the medium, to whom all the secrets of the universe are revealed. The language of his poetry reflects the representation of his lyric hero about the three-component world, which consists of the upper, middle and lower tiers. His lyric hero is aware of the HIGHER WORLD as a world of the divine, a world of eternal truths and laws, a world of angels and pure poetry. The main images that fill this world are the images of sun, sky, bird and wind. One of the central concepts that actualize the locus of the MIDDLE WORLD (or world of the earth) in Oleksii Dovhiy's poetic universe is the image-concept of the LAND. This image is an expression of such lexical and semantic variants of the land tokens as ‘the native land (Ukraine)ʼ and ‘the upper layer of the earth's crust; soil that is cultivated and used for growing plantsʼ. THE UNDERGROUND WORLD is updated by entering the words «field» and «shadow» in the text. As research has shown, the image of the road in Oleksii Dovhiy's poetic space is one of the central ones, since, firstly, the verbalizers of this image often act as components that make up the macro-image of the MIDDLE WORLD, and secondly, the image is combined different time shades in the horizontal spatial plane of the author's world plane. THE UNDERGROUND WORLD is represented in most cases by tokens that are associated with other spatial tiers. However, by entering into the text, such units as «shadow» and «field» acquire contextually predetermined semantic nuances that associatively associate with the lower tier.

У статті проаналізовано характер мовної експлікації уявлень ліричного героя Олексія Довгого про особливості світобудови та організацію Всесвіту. Автором розглянуто такі питання загальнотеоретичного значення, як концепт та мовна картина світу. Під час проведення дослідження було з’ясовано, що поезія Олексія Довгого поєднує в собі одкровення сина, який пишається славою поколінь, батьківськими і дідівськими моральними принципами, сповідь борця за Вітчизну, манускрипт медіума, якому відкриті всі таємниці Всесвіту, погляд філософа, педагога і медитативного лірика. У мові його поезії відображено уявлення його ліричного героя про трикомпонентний світ, який складається з верхнього, середнього та нижнього ярусів. Його ліричний герой усвідомлює ГОРІШНІЙ СВІТ як світ божественний, світ вічних істин і законів, світ янголів та чистої поезії. Основними образами, які наповнюють цей світ, є образи сонця, неба, птаха і вітру. Одним із центральних понять, що актуалізують локус СЕРЕДНЬОГО СВІТУ (або світу земного) у поетичному Всесвіті Олексія Довгого, є образ-концепт ЗЕМЛЯ. Цей образ виступає виразником таких лексико-семантичних варіантів лексеми «земля», як ʻрідний край (Україна)ʼ та ʻверхній шар земної кори; ґрунт, який обробляється і використовується для вирощування рослинʼ. ПІДЗЕМНИЙ СВІТ актуалізується у тексті лексемами «поле» та «тінь». Як показало дослідження, образ дороги в поетичному просторі Олексія Довгого є одним із центральних також, оскільки, по-перше, вербалізатори цього образу часто виступають компонентами, які творять макрообраз СЕРЕДНЬОГО СВІТУ, а по-друге, зазначений образ поєднує у горизонтальній просторовій площині авторського Всесвіту різні часові відтинки. Виразниками ПІДЗЕМНОГО СВІТУ є в більшості випадків лексеми, пов’язані з іншими просторовими ярусами. Однак, потрапляючи в художній текст, такі одиниці, як «тінь» і «поле» набувають контекстуально зумовлених семантичних відтінків, які асоціативно пов’язуються із нижнім ярусом.
Біля витоків поетичного космосу Олексія Довгого
Keywords: cosmology; the Universe; linguistic worldview; Oleksii Dovhiy's poetry; космологія; Всесвіт; мовна картина світу; поезія Олексія Довгого